Weighing the necessities and concerns of deprescribing among older ambulatory patients and primary care trainees: a qualitative study - Goh, Sheron Sir Loon; Lai, Pauline Siew Mei *; Siti Nurkamilla, Ramdzan; Tan, Kit Mun (BMC, 2023)
Background: Deprescribing can be a challenging and complex process, particularly for early career doctors such as primary care trainees. To date, there is limited data from patients' and doctors' perspectives regarding the deprescribing of medications in older persons, particularly from developing countries. This study aimed to explore the necessities and concerns of deprescribing in older persons among older ambulatory patients and primary care trainees.